On the Economic Aspects of Unemployment: The Case of Consumer Confidence - Caleiro, António (2016)
Unemployment is related to economic, political and social aspects. One of the least analysed economic aspects is the relationship of unemployment to the level of confidence that characterizes some macroeconomic relevant agents, such as consumers or investors. Expanding previous work on this matter, this chapter considers a fuzzy logic methodology in order to uncover the relationship that exists between the unemployment rate and the consumer confidence level for a large group of European Union countries, in the period 1995-2015. It is concluded that this relationship is stronger than apparently it looks, especially in certain countries. This result should therefore be used as an extra argument in making economic decisions leading to the diminishment of unemployment, which will boost economic confidence.